Galen's Institutio Logica English Translation, Introduction, and Commentary - Kieffer, John Spangler (Johns Hopkins University Press, 1964)
Originally published in 1964. This book is a translation of Institutio Logica, which was probably written by Galen, although scholars disagree on the possibility of this work being a forgery. It provides a survey on the history of logic written around the third century.